Analysis Of Distortion For Islamic Terms Used In English Textbooks For Islamic University Students Based On Al-Faruqi’s Concept - Setiawan, Edi (Publikasi Indonesia, 2023)
Islam taught by Rasulullah S.A.W, reached its golden age and became a reference to world civilization during the Umayyah, Abbasiah, and other dynasties which finally collapsed during the Ottoman Turks (1924 AD) which later made western civilization a reference point for civilization in this world. Under these conditions a big idea emerged to restore the glory of Muslims, especially in the field of science, the concept was known as the Islamization of knowledge, by Syed Naquib Al-Attas and Ismail Raji Al-Faruqi. From the two scientists, Al-Faruqi specifically made the concept of Islamization of knowledge in the context of teaching English by making a guide book